Chapter The place for ethnography. An academic ethnographic center in the space of the city of Łódź - Deredas, Anna (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
The article presents the history of location and moving to new places of the current Institute of Ethnology and Cultural Anthropology of the University of Łódź. Its subsequent seats from year 1945 to the present day are discussed. The text uses both archival documents and memories of employees and former students.